Barriers, enablers and motivators of the “I’m an active Hero” physical activity intervention for preschool children: a qualitative study - Al-walah, Mosfer A.; Donnelly, Michael; Heron, Neil (Frontiers in Pediatrics, 2024)
Background Insufficient physical activity (PA) in early childhood is linked to adverse health outcomes and a heightened risk of obesity. Successful PA programmes often require input from key stakeholders, such as parents and educators. However, research on stakeholders’ perspectives regarding PA programmes for preschool children is limited, impeding effective programme design and implementation. Objectives This study aims to explore the perspectives of key stakeholders to gain insights into the challenges, facilitators, and motivators that influence the planning, execution, and sustainability of the “I'm an Active Hero (IAAH) intervention component,” a preschool-based initiative designed to promote PA among young children. Methods Semi-structured interviews were conducted in Saudi Arabia with individual preschool principals (n = 2), and focus group discussions were held, respectively, with preschool staff members (n = 4, all female) and parents (4 mothers, 5 fathers). Results A thematic analysis identified four main themes: (1) Barriers to parental involvement in preschool PA interventions, such as time constraints, lack of flexibility, limited space, and a shortage of trained staff; (2) Risks and benefits of children's programme participation; (3) Motivators including rewards, non-financial incentives, and concerns about childhood obesity and a sedentary lifestyle; (4) Facilitating factors for overcoming barriers, including staff training, time reallocation, staff coordination, space optimization, non-financial incentives, and sustaining partnerships. Conclusion This study's findings are crucial for childcare professionals, preschools, education authorities, and policymakers, offering valuable insights for future research. However, further collaboration with key stakeholders is essential to enhance individual attitudes and preschool policies for effective intervention implementation.